Structure-Based Design, Synthesis, and Biological Evaluation of the Cage–Amide Derived Orthopox Virus Replication Inhibitors - Mozhaitsev, Evgenii S.; Suslov, Evgeniy V.; Rastrepaeva, Daria A.; Yarovaya, Olga I.; Borisevich, Sophia S.; Khamitov, Edward M.; Kolybalov, Dmitry S.; Arkhipov, Sergey G.; Bormotov, Nikolai I.; Shishkina, Larisa N.; Serova, Olga A.; Brunilin, Roman V.; et al. (Viruses, 2022)
Despite the fact that the variola virus is considered eradicated, the search for new small molecules with activity against orthopoxviruses remains an important task, especially in the context of recent outbreaks of monkeypox. As a result of this work, a number of amides of benzoic acids containing an adamantane fragment were obtained. Most of the compounds demonstrated activity against vaccinia virus, with a selectivity index SI = 18,214 for the leader compound 18a. The obtained derivatives also demonstrated activity against murine pox (250 ≤ SI ≤ 6071) and cowpox (125 ≤ SI ≤ 3036). A correlation was obtained between the IC50 meanings and the binding energy to the assumed biological target, the p37 viral protein with R2 = 0.60.